On -Line UPS with Low Frequency Transformer for Isolation - Hussein, Husham Idan (Iraqi Journal for Electrical and Electronic Engineering, 2014)
This paper addressed the design of online uninterruptible power supply (UPS) system with a low frequency transformer for isolation, based on given specifications which include bypass switch and battery and taken into account the concentrated on open loop operation. Depending on the application, the online UPS system is composed by two stage conversions of AC/DC and DC/AC, the enclosure of these freeloading effects of all components and devices is very important to design the UPS system for acceptable performance. The initial stage of the design is based on the theoretical calculations and few assumptions have been made throughout the design. Simulation work has been carried out by MATLAB/Simulink program to validate the operation of the online UPS system with low frequency transformer isolation. The analysis of the results are presented and the justifications with regards to performance evaluation parameters which some are not satisfied the design specifications are discussed in details.